“Landscape and Heritage of Hydroelectricity in Portugal” - Matos, Ana Cardoso de (2012)
Hydroelectric power plants provided countries with scarcity of coal, such as Portugal, with a vital source of energy for the production of electricity in large quantities. Therefore, since the late 19th century the use of waterfalls as producers of electric power was a topic of study and interest among engineers and the matter was regularly discussed at the Association of Portuguese Civilian Engineers. The great hydroelectric power plants, considered by many as the cathedrals of the second industrial revolution are an important industrial heritage which is important to value and appreciate. Hydroelectricity also gave origin to new landscapes and the problem today regards the management of this new landscape and the construction of new patrimonial values.